2004
DOI: 10.1111/j.0001-6349.2004.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality after total vs. subtotal hysterectomy

Abstract: Both TAH and SAH significantly reduce dyspareunia without having a negative effect on sexual function. The shift toward SAH seems unwarranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 29 publications
6
53
1
15
Order By: Relevance
“…The remaining one, in addition to five randomized controlled trials showed no difference (20,(38)(39)(40)(41)(42).…”
Section: Anaesthesia-related Complicationsmentioning
confidence: 95%
“…The remaining one, in addition to five randomized controlled trials showed no difference (20,(38)(39)(40)(41)(42).…”
Section: Anaesthesia-related Complicationsmentioning
confidence: 95%
“…The war taking five years increases the child deaths under age of 5 by 13%. Also 47% of all the refugees in the world and 50% of asylum seekers and displaced people are women and girls and 44% refugees and asylum seekers are children under the age of 18 (5). As the result of wars and armed conflicts, women are the current study was conducted to explore the sexual experience of women after hysterectomy.…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%
“…Other authors like Zobbe et al found respectively 60% and 50% no changes in sexuality. 11 The sexual recovery has been effective in 44 patients or 88% within 3 months after hysterectomy. Also note that 44% of women have seen a change in their sexual life.…”
Section: Post Hysterectomy Sexual Experiencementioning
confidence: 99%